A comprehensive investigation on macro–micro crack interactions in functionally graded materials using ordinary-state based peridynamics. (1st May 2022) - Ozdemir, M.; Imachi, M.; Tanaka, S.; Oterkus, S.; Oterkus, E.
Abstract: In the present work, interactions between a macro-crack and various micro-crack configurations are studied extensively. Influence of different micro-crack configurations on propagation of a main crack is numerically examined by ordinary state-based peridynamics. Certain micro-crack configurations improve toughness of the specimens, while the some only has marginal impact on the crack growth rate. Furthermore, very complex crack patterns are effectively simulated by the present implementation of ordinary state-based formulation.